Organizational Culture and Quality Management System Practices of a Private Insurance Company in the Philippines - Jared Russel B. Bautista; Shaira Mae A. Cereno; Azel Marie D. Ayco; Jesus P. Briones; Marmelo V. Abante (People and Behavior Analysis, 2026)
A supportive organizational culture, which provides the foundation for excellence, is vital to implementing an effective quality management system (QMS) in any organization. This study examined how organizational culture influences the QMS practices in a private insurance company in the Philippines. The main objectives included identifying the organization's cultural aspects, assessing QMS practices, analyzing the relationships among those variables, and identifying challenges and barriers to QMS implementation. Using a descriptive-quantitative approach, data were collected from 129 employees of the subject private insurance company via a researcher-developed questionnaire distributed via Google Forms. Data analysis employed descriptive statistics (frequency, percentage, standard deviation, and weighted mean) and Spearman's rho for correlation analysis. Findings showed strong alignment with cultural values, including mission, leadership, and communication, though employee engagement indicated potential for greater involvement in quality initiatives. The QMS assessment emphasized customer satisfaction and quality assurance and recognized the need for consistent documentation. However, employees showed low levels of involvement in QMS training programs and uneven participation across departments, indicating the need for appropriately aligning training with quality objectives. This study confirmed that a supportive organizational culture positively and significantly correlates with the effectiveness of QMS practices, providing evidence that influential culture can help organizations overcome challenges to more effective QMS implementation. Therefore, this study can serve as a model for other organizations to enhance their QMS practices to better serve their stakeholders.